الأساليب الإقناعية لدى صانعي المحتوى على مواقع التواصل الاجتماعي و دورها في التأثير على المستخدمين - لقرع فاطمة الزهراء; لحاق فاطمة; د/معيزة سليم (جامعة عمار ثليجي الاغواط, 2023)
غدت تكنولوجيات الإتصال الجديدة أداة تغيير فعالة ،حيث أصبحت رافعة أساسية لتفعيل نشاط المؤثر عبر مواقع التواصل الاجتماعي ،هذا النشاط الذي غير مفاهيم التأثير عبر شبكة الإنترنت بشكل كبير ورجح الكفة لصالح نمط التأثيري على حساب الأنماط التقليدية الأخرى. لقد تركزت إشكالية دراستنا على دور المؤثر عبر مواقع التواصل الاجتماعي، من خلال دراسة استكشافية شملت متابعي صفحة خبيب على الفيسبوك ،حيث انطلقنا من الإطار المنهجي المفاهيمي وقمنا بتطبيق المنهج المسحي بشقيه الوصفي والتحليلي ،كان ذلك عن طريق استخدام استمارة استبيان قمنا بتوزيعها إلكترونيا ،كما اعتمدنا على تحليل الشبكات الاجتماعية كأداة مساعدة ،بعد ذلك جاء الإطار النظري الذي تناولنا فيه ثلاث فصول تضمنا المادة العلمية للدراسة. ثم جاء الإطار التطبيقي الذي يمثل الجانب الميداني للدراسة وحوصلة لبحثنا هذا. وقد توصلنا إلى مجموعة من النتائج أهمها أنّ دور المؤثّر في التأثير على مستخدمي مواقع التواصل الإجتماعي "متوسط قريب من الفعّال" حسب رأي المبحوثين عموما ،كما استنتجنا أنّ مؤثر يعدو من بين الشخصيات الأكثر متابعة على موقع الفيسبوك، ما يدل على الدور الذي يمكن أن يلعبه المؤثرون في شتى المجالات عبر مواقع التواصل الاجتماعي . كلمات مفتاحية: صناع ة المحت وى ، وسائل التواصل الاجتماعي.Sammary: New communication technologies have become an effective tool for change, as they have become an essential lever for activating the activity of influencers through social networking sites, this activity that has changed the concepts of influence via the Internet significantly and tipped the balance in favor of the influencer style at the expense of other traditional styles. The problem of our study focused on the role of influencers through social networking sites, through an exploratory study that included the followers of Habib's page on Facebook, where we started from the conceptual methodological framework and applied the survey approach, both descriptive and analytical, by using a questionnaire form that we distributed electronically, and we also adopted On the analysis of social networks as an auxiliary tool, then came the theoretical framework In which we dealt with three chapters that included the scientific material for the study. Then came the applied framework that represents the field aspect of the study and the outcome of our research. We have reached a set of results, the most important of which is that the role of influencers in influencing users of social networking sites is "average". close to effective" according to the respondents' opinion in general, and we also concluded that social media influencers are among the most followed personalities on Facebook, which indicates the role that influencers can play in various fields through social networking sites. Keywords: Content industry, Social Media.
على عينة من متابعي صفحة خبيب "khoubi"على الفيسبوك-